DESIGN THINKING AND DIGITAL ENTREPRENEURSHIP: INNOVATIVE APPROACHES TO BUSINESS PLANNING IN THE DIGITAL AGE - BEI, Hanna; PANCHENKO, Igor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the conceptual substantiation of the application of design thinking in digital entrepreneurship as an innovative approach to business planning in the digital age. The key features of digital transformations that define new requirements for entrepreneurial activity, strategic planning and implementation of entrepreneurial ideas are outlined. The main tangible and intangible advantages provided by digitalization to entrepreneurship and business management are characterized. The scientific category of ‘design thinking’ is analyzed and the conceptual dimensions of its study are defined, covering the evolution of the concept from the moment of its first application to the modern human-centered paradigm. The author’s vision of integrating the principles and methodology of design thinking into business planning processes in the development of digital startups, as well as building asynchronous models of creating consumer value, is presented. A typical scheme (framework) for applying design thinking in business planning in the digital era is formulated. The key obstacles to the application of design thinking in modern entrepreneurship are substantiated due to the underdevelopment of personal skills of managers and executives that contribute to the proper integration of design thinking into the ecosystem of business planning of enterprises. The application of design thinking in digital entrepreneurship involves a significant shift from traditional methods of business planning, emphasizing a more flexible, iterative, and user-centric approach. By focusing on empathy, ideation, and experimentation, design thinking enables entrepreneurs to better understand and meet the needs of their customers, thus fostering innovation and enhancing competitive advantage. However, the successful implementation of design thinking in business planning is not without challenges. Furthermore, the integration of design thinking into existing business structures and cultures often requires a significant shift in mindset and organizational practices, which can be difficult to achieve without strong leadership and a clear vision. Despite these challenges, the benefits of incorporating design thinking into digital entrepreneurship are substantial, offering a pathway to more innovative, customer-focused, and agile business practices that are well-suited to the demands of the digital age.